Conflict Management in Islamic Organizations: Integrating Sharia Principles for Organizational Harmony and Growth - Shita Dwi Ariani; Iqbal Aditia; Sumarta (Lentera Peradaban: Journal on Islamic Studies, 2026)
Conflict is an inseparable part of organizational dynamics, including within Islamic organizations characterized by the diverse traits of their members. This study aims to analyze conflict management practices in Islamic organizations by highlighting the implementation of Sharia principles as the primary foundation for dispute resolution. This research employs a literature review method, referencing accredited scientific sources from the last 5–10 years to ensure data validity and currency. The findings indicate that conflict should not necessarily be viewed as a threat but rather as an opportunity for growth, innovation, and the strengthening of ukhuwah Islamiyah (Islamic brotherhood). Principles such as shura (consultation), ishlah (mediation/reconciliation), justice, and patience serve as the bedrock for building an organizational culture that is harmonious, fair, and sustainable. Unlike conventional conflict management, which focuses on efficiency and rapid resolution, the Islamic approach emphasizes harmony, substantive justice, and long-term blessings (barakah). Thus, Sharia-based conflict management fosters a productive, inclusive, and resilient work environment while reinforcing the unity and solidarity of the ummah. This research offers practical benefits for foundation managers, Islamic organization leaders, and the academic community in developing conflict management models aligned with divine values.